ANALYSIS OF THE FINANCIAL PERFORMANCE OF THE REGIONAL GOVERNMENT OF BENGKULU PROVINCE: THE DEGREE OF FISCAL DECENTRALIZATION APPROACH - Setiawan, Feri; Hermanto, Bambang Agoes (Yayasan Nuraini Ibrahim Mandiri, 2025)
The objective of this study is to utilize an empirical approach to analyze the financial performance of the Regional Government of Bengkulu Province in relation to the degree of fiscal decentralization. The secondary data set employed in this study offers a valuable opportunity to examine the financial performance of the Bengkulu Provincial Government. The empirical results obtained from this study indicate that the financial performance of the Provincial Government is suboptimal due to the significant disparity between the Public Accountant's Report (PAD) and total revenue. Furthermore, the analysis reveals that local taxes, local levies, and other PADs have a positive and significant effect on the financial performance of Bengkulu Province. Conversely, capital expenditure has been found to exert a negative and significant influence on the financial performance of the Regional Government of Bengkulu Province, underscoring the need for a more autonomous local government budgetary process. The findings of this study indicate that local governments in Bengkulu Province continue to rely heavily on central government transfers, indicating a significant need for greater financial autonomy.